PELUANG PEMANFAATAN TERAPI LASER AKUPUNKTUR SEBAGAI ADJUVAN PEMBENTUKAN ANTIBODI TERHADAP PASIEN PASKA VAKSINASI VAKSIN SINOVAC - Flora Eka Sari (Universitas Islam Negeri Alauddin Makassar, 2024)
Vaccination is often really needed by the community, especially in pandemic conditions, namely when the formation of antibodies is needed quickly, so that the vaccine's permit is considered an emergency decision. The formation of vaccine antibodies also depends on adjuvants, namely substances added to strengthen the formation of antibodies. The most commonly used adjuvants are aluminum salts, but they are not always optimal. The adjuvant view of vaccines can shift to a holistic meaning that is bioenergetic and homeostatic. For this purpose, the vaccine can be optimized with a 650nm bioenergetic laser administered at acupuncture points, becoming a vaccine adjuvant. The purpose of this study was to provide an overview of the benefits of laser acupuncture as a vaccine adjuvant, namely to increase antibodies and administer vaccines. This research wants to prove the increase in Sinovac vaccine RBD antibody titer, which at the beginning. This research method is a two-group, two-posttest only design (observational) with a control group and purposive sampling in collaboration with Lakespra and laboratory approval, starting in early February 2022 and ending in March 2022. Subjects who met the inclusion and exclusion criteria were given vaccine administration according to their group, and then blood specimens were taken for RBD antibody testing. The data was evaluated to see the increase in antibodies after the first and second vaccines compared to the control group of the prediction was in doubt about the formation of antibodies.